The complete mitochondrial genome of Rhynchocypris czekanowskii (Cypriniformes, Cyprinidae) - Yin-Tao Zhang; Cheng-Pu Lu; Yu-Hui Tao; Cheng-Wei Tong; Jie Chen; Wei Liu (Mitochondrial DNA. Part B. Resources, 2025)
Here we present the first complete mitochondrial genome assembly of Rhynchocypris czekanowskii Dybowski, 1869. We characterized a 16,651-bp circular genome comprising 13 protein-coding genes, 22 tRNA genes, 2 rRNA genes, and a 981-bp control region. Phylogenetic reconstruction using mitochondrial sequences robustly resolved R. czekanowskii as sister to R. lagowskii (bootstrap = 100%), supporting morphological affinities. This work fills a critical genomic gap in Rhynchocypris phylogenetics and has significant implications for both taxonomic revision and the conservation of cold-adapted ichthyofauna in Northeast Asia.